Профілактичний вплив гумінової біологічної добавки на мітохондрії печінки монгольських піщанок - Дьомшина, Ольга; Dyomshyna, Olga; Ушакова, Галина; Ushakova, Galyna; Степченко, Лілія Михайлівна; Stepchenko, L.; Stepchenko, L. M.; Stepchenko, Lilia M.; Stepchenko, Lilia (ДНУ ім. О. Гончара, 2022)
Доведено профілактичну підтримку антиоксидантної системи, стимуляцію функціональної активності мітохондрій печінки на фоні застосування Гуміліду на дорослому етапі життєдіяльності тварин. Humilid is a nutritious, biologically active additive that contains humic substances. Most organic materials in mineral soils are humic substances that are highly heterogeneous groups of acidic macromolecules. Humic acids and their salts in organic substances were represented as 50-58% in the applicated Humilid. Long-term studies of the properties have proven its powerful biological effect on animal organisms.
The preventive impact of humic biological add on mitochondria liver Mongolian Gerbils
Степченко Лілія Михайлівна https://orcid.org/0000-0001-8509-7048
Keywords: антиоксидантна система; antyoksydantna systema; гумінові біологічні добавки; huminovi biolohichni dobavky; Гумілід; Humilid